Antibacterial Activity of Cassia tora Leaves - Kadam, R.T. Chavan, V.L. Deshmukh and A.S. (Recent Research in Science and Technology, 2011)
Ethanolic and aqueous extracts from the leaves of Cassia tora were investigated for their antibacterial activity. Their concentrations 0.15mg, 0.31mg ethanolic and aqueous extracts respectively were studied in activity, which involved the determination of inhibition zone in mm. Both the extracts exhibited significant antibacterial activity. Ciprofloxacin used as standard reference. The antibacterial activity of ethanolic and aqueous extracts of Cassia tora has therefore been demonstrated for the first time.